Verticality, Regulatory Focus, and Prices: Who is Able to Get a Good Deal? - Marconi Freitas da Costa; Claudio Felisoni de Angelo; Salomão Farias (BBR: Brazilian Business Review)
The use of the metaphor of verticality may affect consumers’ motivations to perform product price assessments, and the motivational regulatory focus of the individual may have features that contribute to restoring motivation. This study aims to analyze the influence of the verticality metaphor, and of the regulatory focus on price assessments in order to get a good deal. We performed an experimental study with a design 2 (vertical metaphor: physically tall vs. physically short) x 2 (regulatory focus: promotion vs. prevention) between subjects. The results show that the treatment group, with the individuals who consider themselves physically tall and focused on prevention, had the best performance when assessing price in the context of getting a good deal. The originality of this research lies in the identification of the behavioral characteristics of individuals that are able to mitigate changes in people’s motivation when exposed to mental simulations of verticality, in order to get a good deal. In practical terms, the findings make it evident that the decrease in individuals’ motivation for decision making surrounding prices, under the effects of verticality, can be reestablished when they take on surveillance behavior as well as behavior aimed at avoiding mistakes.